Ovarian hormones and eating disorders - Young, John K. (Frontiers in Psychology, 2024)
The goals of this minireview are to 1) briefly review the genetic, physiological, and psychological features of anorexia nervosa and bulimia nervosa, 2) examine recent data about how sex hormones could contribute to the dramatic sex differences in the incidence of these disorders, and 3) propose mechanisms by which mutations in genes linked to anorexia nervosa could lead to abnormalities in the brain response to estrogen. These goals conform to the guidelines listed for the scope of Frontiers in Psychology/eating behavior subset.